PENGARUH KEBIJAKAN HUTANG, PROFITABILITAS, LIKUIDITAS DAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Fahrul, Muhammad; Dewi, Siska (Jurnal Akuntansi dan Bisnis, 2023)
This research aims to obtain empirical evidence regarding the influence of debt policy on company value, profitability on company value, liquidity on company value, and corporate governance on company value in manufacturing companies in the food and beverage industry sub-sector. This type of research is quantitative research. The population in this research are manufacturing companies in the food and beverage industry sub-sector listed on the Indonesia Stock Exchange during 2018-2022. Determining the sample in the study used a purposive sampling method with the criteria of food and beverage companies that did not experience minus equity, companies that did not experience losses, companies that had independent commissioners, companies that published complete financial reports for the 2018-2022 period so that a sample of 9 companies was obtained. The analysis technique of this research uses multiple linear regression analysis. The research results show that debt policy and profitability have a significant effect on company value. Meanwhile, liquidity and corporate governance have no effect on company value. Keywords: Debt Policy, Profitability, Liquidity, Corporate Governance, Firm Value